Pendidikan Karakter : Analisis ‘Ibad al-Rahman Dalam Surah Al-Furqan: Character Education: An Analysis of ‘Ibad al-Rahman in Surah al-Furqan - Suhaimi, Khadijah Munirah; Azmi, Riswadi; Sabri, Nor Hazmin; Dollah @ Abdullah, Aisyah (Jurnal Usuluddin, 2022)
The social problems that occur in society require various approaches to overcome. Among the ideal approaches to highlight is character education. This is because character education is an approach that can change the character of the individual to become a better person. In fact, the Quran has displayed many characters that need to be emulated and shunned through stories and lessons. Among the character education that needs to be highlighted is verses 63-74 of surah al Furqan which is also known as 'ibad al-Rahman. Looking at the importance of character education in the Quran, this study aims to examine the concept of 'Ibad al-Rahman contained in surah al-Furqan and identify the characters of 'Ibad al-Rahman which can be highlighted from it. Qualitative study methods are used by examining past studies and library studies. The results of the study found that 'ibad al-Rahman is a group of verses that explain the beloved servant of Allah and should be practiced by every Muslim. The results of the study also found that there are 10 characters contained in the verses covering two aspects, namely the human relationship with the creator and the relationship of man with man. This study is seen to be able to give the public an understanding of the importance of character education based on the Quran.